Exploring molecular signatures related to the mechanism of aging in different brain regions by integrated bioinformatics - Su, Xie; Xie, Lu; Li, Jing; Tian, Xinyue; Lin, Bing; Chen, Menghua (Frontiers in Molecular Neuroscience, 2023)
Background. The mechanism of brain aging is still far from being fully understood. Currently, few studies try to find the Molecular change by bioinformatics at subregional level in aging brain. Therefore, this study aimed to find the molecular signatures and key genes of aging depend on brain region. Methods. Differentially expressed genes (DEGs) of aging of cerebral cortex (CX), hippocampus (HC) and cerebellum (CB) were identified respectively based on 5 datasets from Gene Expression Omnibus (GEO). Molecular signatures of aging were explored by functional and pathway analysis. Hub genes of each brain region were determined by protein–protein interaction (PPI) network analysis and the common expressed DEG (co-DEG) was also found. Gene-microRNA (miRNA) and gene-disease interaction were constructed by online databases. The expression levels and regional specificity of hub genes and co-DEG were validated by animal experiment. Results. 32, 293 and 141 DEGs were identified for aging of CX, HC and CB respectively. Enrichment analysis showed that molecular change related to leukocyte invasion, abnormal neurotransmission and impaired neurogenesis due to the inflammation may be the major signatures of CX, HC and CB respectively. Itgax was the hub gene of cortical aging. Zfp51 and Zfp62 were the hub genes of hippocampal aging. Itgax and Cxcl10 were the hub gene of cerebellar aging. S100a8 was the only co-DEG of all the three regions. In addition, a series of molecular changes associated with inflammation were found in all the three brain regions. Several miRNAs were interacted with the hub genes and S100a8. The level change of genes was further validated in animal experiment, but only the upregulation of Zfp51 and Zfp62 were restricted to HC. Conclusion. The molecular signatures of aging have regional differences in the brain and seem to closely relate to the neuroinflammation. Itgax, Zfp51, Zfp62, Cxcl10 and S100a8 may be the key genes and potential targets for prevention of the brain aging.